x-15=(-2

Simple and best practice solution for x-15=(-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-15=(-2 equation:



x-15=(-2
We move all terms to the left:
x-15-((-2)=0
We add all the numbers together, and all the variables
x=0

See similar equations:

| 4/x-3=12/x+1 | | 10=21-3(-4-4w) | | 10x-6=14+3(2-x) | | 10a/2+4.84=6+10.648a | | r+34=24 | | 18c-10c-13c=20 | | 52+8w=164 | | 10x-7=5x-14 | | 12x+2-4x=4(2x+2) | | y^2+-8y=-11 | | 2a=-10a+48 | | 5g+10=1g+3 | | -5=55x-16x^2 | | (85+60+s)/3=70 | | 12x+2-4x=6(2x+3) | | y2+-8y=-11 | | 4.1+10x=6.59 | | 15+18-5=7x | | 0.3(2w+10)=0.6w+3 | | 3(w-8)-6w=-6 | | -7p-9=-7p+10 | | 2x+7+5x-7=4x+9 | | 7(3y-2)=19 | | 5n=-36+14n | | -5m-7=-4m | | 9j+10=10+9j | | 4.1+10m=7.38 | | 0.4x-0.04x=0.12(1.92-x) | | -3q-6=-2q+4 | | 75b=3b-16 | | -3(6y-3)+6y=-3(y+2) | | 1=z/2-3 |

Equations solver categories